Basic Studies Aiming at Orius minutus (Hemiptera: Anthocoridae) Mass-Rearing - Hye-Jeong Jun; Kyoung-Su Kim; Eun-Hye Ham (Insects, 2022)
This study presented biological and economic data for the mass-rearing of Orius minutus in Korea. Simplifying the mass-rearing process through an alternative diet and an artificial oviposition substrate is a prerequisite for enhancing the usability of this insect as a biological control agent. We compare the hatch rate of O. minutus eggs deposited on a plant substrate with that of eggs deposited on two artificial substrates, cork sheets and rubber. The results indicate that cork sheet is the most cost-effective artificial oviposition substrate for the mass-rearing of O. minutus. We also examine five feeding treatments that included two types of brine shrimp eggs and eggs of Ephestia cautella to compare the number of eggs laid in the fifth generation. We found no significant difference between the two treatment groups; 61.3 eggs were laid in the treatment group fed iron-coated brine shrimp and moth eggs, and 67.4 eggs were laid in the control group. The plant-free model developed in our study can reduce rearing costs by 70.5% compared to the conventional mass-rearing model.